The effect of fiber post location on fracture resistance of endodontically treated maxillary premolars - Sulaiman, Eshamsul; Alarami, Nada; Wong, Yuh Ing; Lee, Wen Hui; Al-Haddad, Afaf (Wroclaw Medical University, 2018)
Background. There is no sufficient literature on the effect of post location on endodontically treated premolar teeth with 2 roots. Objectives. The aim of the study was to evaluate the effect of fiber post location on fracture resistance and failure mode of endodontically treated premolars with 2 roots. Material and methods. Fifty extracted maxillary first premolars with 2 roots were divided randomly into 5 groups. Group 1 was comprised of sound teeth, which received only metal crowns (control). Teeth from groups 2, 3, 4, and 5 were decoronated 2 mm above the cementoenamel junction (CEJ) and were endodontically treated. No post was placed in group 2 teeth. Teeth from groups 3, 4 and 5 were given a fiber post placed in the buccal canal, palatal canal, and both buccal and palatal canals, respectively. All teeth in groups 2, 3, 4, and 5 were built up with composite and full coverage metal crowns. A compressive static load was applied at an angle of 25 degrees to the crowns with a crosshead speed of 0.5 mm/min, until fracture. Results. One-way analysis of variance (ANOVA) showed significant differences among the groups (p = 0.002). A post hoc test showed significantly lower fracture resistance of group 4 compared to group 5 (p = 0.011). Furthermore, group 2 had significantly less fracture resistance compared to group 1 (p = 0.021) and group 5 (p = 0.002). According to Fisher's exact test, different post locations are non-significantly associated with fracture mode (p = 0.256). Conclusions. Fiber post location has a significant effect on fracture resistance of severely damaged, endodontically treated maxillary premolars with 2 roots. However, post placement in the palatal root is preferred, as it maintains the restorability of the tooth.